Radio and X-ray study of two multi-shell supernova remnants: Kes 79 and G352.7-0.1 - Giacani, Elsa Beatriz (2009)
Aims. We investigate two multi-shell galactic supernova remnants (SNRs), Kes 79, and G352.7−0.1, to understand the causes of this morphology. Methods. The research was carried out based on new and reprocessed archival VLA observations and XMM-Newton archival data. The surrounding gas was investigated based on data extracted from the HI Canadian Galactic Plane Survey, the 13CO Galactic Ring Survey, and the HI Southern Galactic Plane Survey. Results. The present study infers that the overall morphology of both SNRs is the result of the mass-loss history of their respective progenitor stars. Kes 79 is likely to be the product of the gravitational collapse of a massive O9 star evolving near a molecular cloud and within the precursor’s wind-driven bubble, while G352.7−0.1 should be the result of interactions of the SNR with an asymmetric wind from the progenitor together with projection effects. No radio point source or pulsar wind nebula was found to be associated with the X-ray pulsar CXOU J185238.6+004020 in Kes 79. The X-ray study of G352.7−0.1 found that most of the thermal X-ray radiation completely fills the interior of the remnant and originates in heated ejecta. Characteristic parameters, such as radio flux, radio spectral index, age, distance, shock velocity, initial energy, and luminosity, were estimated for both SNRs.